Analysis of Alternative Strategies for Domestic Wastewater Systems Management and Development in Regency/City Governments (Case Study: South Tangerang City, Banten Province) - Nur Dewisri Fatihawati; Marisa Handajani (International Journal Labs, 2022)
The impact of high urban population growth and increasing development activities in various sectors causes various problems in urban areas, one of which is wastewater pollution. Through the